2019
DOI: 10.1097/ede.0000000000000961
|View full text |Cite
|
Sign up to set email alerts
|

Plant-based Diet and Adiposity Over Time in a Middle-aged and Elderly Population

Abstract: Background: We aimed to explore whether adhering to a more plant-based diet, beyond strict vegan or vegetarian diets, may help prevent adiposity in a middle-aged and elderly population. Methods: We included 9,633 participants from the Rotterdam Study, a prospective cohort in the Netherlands. Dietary data were collected using food-frequency questionnaires at baseline of three subcohorts of the Rotterdam Study (1989–1993, 2000–2001, 2006–2008). We created… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
27
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 43 publications
(45 citation statements)
references
References 24 publications
7
27
1
Order By: Relevance
“…These conflicting results may be explained by the different methods used. The sample size in the Chen et al study was larger and only baseline measurement of dietary intake were available, whereas in the present study food intake was measured at both test moments.…”
Section: Discussionmentioning
confidence: 78%
“…These conflicting results may be explained by the different methods used. The sample size in the Chen et al study was larger and only baseline measurement of dietary intake were available, whereas in the present study food intake was measured at both test moments.…”
Section: Discussionmentioning
confidence: 78%
“…We observed that a more plant-based diet and a lower intake of animal protein are associated with lower insulin resistance over time and lower risk of diabetes, independent of other lifestyle and dietary factors [205,389]. In other analyses we studied several pathways that may link nutrition or physical activity to diabetes risk and metabolic health, such as adiposity [390], inflammatory pathways [391,199] or DNA methylation [392][393][394][395].…”
Section: Main Findings In the Last 3 Yearsmentioning
confidence: 92%
“…For the current analysis within the Rotterdam Study, of the 14,926 participants who participated at baseline, we had dietary data available for 9701. Main reasons for absence of valid dietary data among the 5225 participants were: no dietary data available (n = 4890) including not having received dietary assessment because of logistic reasons, living in a resident home for elderly or suspected dementia, and not having completed the dietary assessment; or excluded as invalid dietary data (n = 335) defined as an estimated energy intake of < 500 or > 5000 kcal/day) [18,19]. From these 9701 participants, we further excluded 1914 participants with CVD, diabetes, or cancer at baseline, and 1 participant without follow-up data on mortality, leaving 7786 participants for the main analyses (Supplemental Figure 1).…”
Section: Study Design and Population In The Rotterdam Studymentioning
confidence: 99%